The Risk Factors of Inhibitor Development and Hepatitis C Virus among Hemophilic Patients in Children Welfare Teaching hospital. - Al-Beldawi, Dhia H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Inhibitor development and HCV are considered the most serious complications of hemophilia treatment. Many factors may increase the risk of complications which include: type of hemophilia, age of the patient, age of onset, duration of the disease, & number of replacement per month. Patients and methods: A descriptive study included 200 patients less than 20 years of age admitted to the Hemophilia Center in Children Welfare Teaching Hospital , medical city in Baghdad , their data ( ag , sex , disease onset and duration , severity of hemophilia ) were collected over 8 months period from 1st January to 31st August 2006. Mixing tests and serology tests for HCV and HBV were performed for all patients. Results: The study showed that 156 (78%) patients had hemophilia A, 44(22%) patients had hemophilia B, and 122 (61%) patients were older than 10 years, in 166 (83%) patients the disease was diagnosed before 2 years of age. Twenty (12.8 %) patients with hemophilia A and 4(9%) patients with hemophilia B developed inhibitors (+ve mixing test). Age more than 10 years, disease onset before 2 years and severe hemophilia were the most common associated findings in patients with inhibitors in 19(79%) , 22(91%), 15(62.5%) patients respectively. Eighty (40%) patients had HCV and 6(3%) patients had HBV, patients older than 10 years , disease duration more than 5 years and severe hemophilia were the most common associated findings with HCV in 68(57.6%), 64 (56%), and 44(45%) patients respectively. Conclusions: The risk of inhibitor development was associated more with Hemophilia A, age more than 10 years, early onset and severe disease but the association was statistically insignificant. The rate of HCV infection was high, that needs special attention and effective screening program.